African potato (Hypoxis hemerocallidea): a systematic review of its chemistry, pharmacology and ethno medicinal properties - Celia M. J. Matyanga; Gene D. Morse; Mazuru Gundidza; Charles F. B. Nhachi (BMC, 2020)
Abstract Background African Potato (hypoxis hemerocallidea), is used for enhancing immune system in Southern Africa. It is among the plants of intense commercial and scientific interest; hence, the aim of this study was to describe its chemistry and pharmacology. Methods PubMed, Cochrane Controlled Trials Register (CENTRAL) and Google Scholar were searched independently for relevant literature. The last search occurred in October 2018. Other research material was obtained from Google. The following search terms were used, but not limited to: "African Potato", "hypoxis", "hemerocallidea", "rooperol." Articles that were explaining the chemistry and pharmacology of hypoxis hemerocallidea were included. Results Thirty articles from PubMed, Cochrane and Google Scholar were eligible. Three webpages were included from Google. Results showed that the tuberous rootstock (corm) of African Potato is used traditionally to treat wasting diseases, testicular tumours, insanity, barrenness, impotency, bad dreams, intestinal parasites, urinary infection, cardiac disease and enhancing immunity. The plant contains hypoxoside, which is converted rapidly to a potent antioxidant, rooperol in the gut. The corm contains sterols, sterol glycosides, stanols, terpenoids, saponins, cardiac glycosides, tannins and reducing sugars. A dose of 15 mg/kg/day of hypoxoside is reportedly therapeutic. Preclinical studies of African Potato have shown immunomodulation, antioxidant, antinociceptive, hypoglycaemic, anti-inflammatory, anticonvulsant, antibacterial, uterolytic, antimotility, spasmolytic and anticholinergic effects. The common side effects of African Potato are nausea and vomiting, which subside over time. In vitro, African Potato demonstrated inhibitory effects on CYP1A2, 2C9, 2D6, 3A4, 3A5, CYP19-metabolism and induction of P-glycoprotein. In vivo, it did not alter the pharmacokinetics of efavirenz or lopinavir/ritonavir. Conclusion African Potato is mainly used as an immunostimulant. The exact mechanisms of action for all the pharmacological actions are unknown. More research is required to substantiate claims regarding beneficial effects. There are many research gaps that require investigation including pharmacokinetic interactions with conventional drugs, especially those used in HIV/AIDS.